The Social Sharing of Emotions (SSE) in the Dominican Republic’s Cultural Context: Autobiographical Descriptive Data - Cantisano Jorge, Nicole; Université de Toulouse 2, Le Mirail URI Octogone-Cerpp (2013)
The propensity to speak and share emotional experiences, denoted as the social sharing of emotions (SSE), has been thoroughly investigated, showing in different cultural settings that 80% to 95% of emotional experiences, negative or positive, are object of SSE. The present study’s main objective was to obtain descriptive data concerning SSE in the Dominican culture. A total of 306 Dominican laypersons responded to a questionnaire which recollected autobiographical data aiming: to establish main SSE descriptive indicators (rate, recurrence and delay) and to identify social sharing targets in this cultural context. Findings corroborate previous studies concerning SSE global indicators. First, this Dominican sample is at comparable levels regarding sharing rates 92.48% of emotional episodes were socially shared. Secondly, 68.62% of participants reported having shared the emotional episode the same day it took place. Third, findings revealed that 72.55% of participants talked about the emotion-eliciting event several times. To conclude, the study’s findings show that Dominican laypersons are at comparable levels as other populations when it comes to SSE indicators and that Dominicans’ choice in social sharing targets, intimates, is compatible with numerous SSE studies (Rimé, 2009).